2011
DOI: 10.4244/eijv7i6a112
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after PCI for acute coronary syndrome in unprotected left main coronary artery disease: insights from the Swiss Acute Left Main Coronary Vessel Percutaneous Management (SALVage) study

Abstract: Acute coronary syndrome due to critical ULM stenosis is associated with high mortality even after successful PCI. Patients presenting with CS or STEMI are at particular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
2
31
0
2
Order By: Relevance
“…Reviewing the literature, there is a worldwide variety in the management of PPCI of ULMCA concerning drug-eluting stent (DES) or bare metal stent (BMS) use. Most of the contemporary European, Australian and Japanese studies reported dominant BMS8 17 or mixed BMS/DES1 3 16 18 21 use, while in the Korean studies, most PPCIs of the ULMCA were performed with DES 9 14 19. Previous large meta-analyses comparing DES with BMS in patients with stable angina/acute coronary syndromes38 and STEMI39 consistently showed no benefit of DES concerning death or MI, whereas revascularisation rates were significantly lower with DES.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the literature, there is a worldwide variety in the management of PPCI of ULMCA concerning drug-eluting stent (DES) or bare metal stent (BMS) use. Most of the contemporary European, Australian and Japanese studies reported dominant BMS8 17 or mixed BMS/DES1 3 16 18 21 use, while in the Korean studies, most PPCIs of the ULMCA were performed with DES 9 14 19. Previous large meta-analyses comparing DES with BMS in patients with stable angina/acute coronary syndromes38 and STEMI39 consistently showed no benefit of DES concerning death or MI, whereas revascularisation rates were significantly lower with DES.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Collateral flow was graded using a classification system developed by Rentrop et al (9) ULMCA disease was defined as a lesion ≥ 50% in the left main artery in the absence of a patent coronary artery bypass graft (CABG) to the left anterior descending (LAD) or circumflex arteries. (10,11) CS was defined as hypotension secondary to cardiac dysfunction (i.e. systolic blood pressure of < 90 mmHg for at least 30 minutes or the need for supportive measures to maintain a systolic blood pressure of ≥ 90 mmHg) and end-organ hypoperfusion.…”
Section: Methodsmentioning
confidence: 99%
“…These recommendations excluded patients presenting acutely with myocardial infarction. Acute coronary syndromes from culprit unprotected left main (ULM) critical stenosis has been associated with significant mortality and morbidity, due to the large area of myocardium at risk . In particular, the subset of ULM acute coronary syndrome (ACS) patients who survive the initial moments following ULM plaque rupture and actually enter the healthcare system with ST elevation myocardial infarction (STEMI) represent a much higher risk cohort with increased adverse outcomes …”
Section: Introductionmentioning
confidence: 99%